COMPARATIVE EVALUATION OF BONDING STRENGTH BETWEEN METAL CERAMIC AND ALL CERAMIC CROWN CEMENTED ON IMPLANT ABUTMENT LUTED WITH RESIN CEMENT - Utpalendu Biswas; Mohammad Abid; Md. Mahbubur Rahman; Rajib Kumar Banik; Mozammal Hossain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This in-vitro investigation was carried out at BSMMU’s Department of Prosthodontics. thirty specimens/crowns in all, made entirely of ceramic materials and with metal. In order to test bonding strength individually, a total of thirty crowns or specimens were luted with resin cement on implant abutments. These specimens’ homogeneous outer layer thickness complied with American Dental Association (ADA) requirements. The two sets of crown specimens had the same inner hole diameter. Based on preset parameters, dental labs produced crowns for both groups. The Universal testing matching system at BUET’s Biomedical Engineering Department was used to administer this test. The bonding strength (MPa) of luting cement between implant abutment and crown specimens was measured using a UTM test. The pre-tested semi-structured check list was utilized to record the specimens’ bonding strength value. Software known as the Statistical Package for Social Sciences (SPSS) (version 24) for Windows was used to verify, amend, code, and analyze the collected data. To find the mean value and its standard deviation for each core material, the bonding strength values were subjected to a t-test analysis. Tables were utilized to display the results. The study’s findings showed how the bond strength value (MPa) of resin cement, which was used as a luting agent in groups I (metal crowns) and II (all ceramic crowns), distributed over the thirty study samples in total (15 samples in each group). According to the study’s findings, group-II (all ceramic crowns) had a mean bond strength value (MPa) of resin cement as a luting agent that is higher than group-I (metal crown). Furthermore, a statistically significant difference (p-value =.001) exists between the mean and standard deviation of the bond strength value (MPa) of resin cement used as a luting agent in groups I (metal crown) and II (all ceramic crown). In conclusion, all ceramic crowns produced a stronger bonding strength than metal ceramic crowns cemented on implant abutments luted with resin cement.